1998
DOI: 10.1111/j.1600-0781.1998.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of minimal erythema dose after water and salt water baths

Abstract: Knowledge about the influence of salt water baths on UV irradiation, especially balneophototherapy, is incomplete. The aim of this study was to investigate the influence of various concentrated salt solutions on the minimal erythema dose (MED). We determined the MEDdry (UVB) in 24 healthy, previously UV unexposed subjects on the inner forearm. Subjects were divided randomly into two groups of 12. Subsequently, the MEDwet was assessed on each forearm after 30 min tap water or 5% salt water bath (group A), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 14 publications
0
26
2
Order By: Relevance
“…A substantial keratolytic effect due to high salinity is unlikely as we measured UV transmission immediately after soaks. Indeed, the aforementioned observations contrast with previous studies showing rather increased UVB-induced erythema reactions after tap water and low-concentration salt water immersions [10,13,14,15]. On the other hand, neither Schiener et al [7] nor Dawe et al [5] observed in their large clinical psoriasis trials an increase in erythemal response to UVB after salt water exposure of different concentrations.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…A substantial keratolytic effect due to high salinity is unlikely as we measured UV transmission immediately after soaks. Indeed, the aforementioned observations contrast with previous studies showing rather increased UVB-induced erythema reactions after tap water and low-concentration salt water immersions [10,13,14,15]. On the other hand, neither Schiener et al [7] nor Dawe et al [5] observed in their large clinical psoriasis trials an increase in erythemal response to UVB after salt water exposure of different concentrations.…”
Section: Discussioncontrasting
confidence: 54%
“…We have previously found a more or less marked decrease in the MED for all liquids studied (tap water; 5, 10 and 20% NaCl solutions). The strongest percentage decrease of the MED (38.6 and 51.4%, respectively) was observed after tap water and 10% NaCl soaks [13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the water itself could remove psoriatic scale [36], which may be beneficial for skin absorption of phototherapy. Previous studies have shown that water bath markedly increased photosensitivity to UVB [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the photosensitivity to UV-B is markedly increased (lower MED) after exposure to tap-water or saltwater baths, but no concentration-dependent effect was found. 38 Other authors found a decrease in MED after baths in tap water or lowconcentration sodium chloride solution (Ͻ4%), but no decrease in MED after a bath in 26% sodium chloride solution. 15 In our study, both MED and cumulative UV doses did not differ between UV-B, TW UV-B, and SW UV-B.…”
Section: -02mentioning
confidence: 97%